Elastic-plastic stresses in a thin rotating disk with shafthaving density variation parameter under steady-state temperature - Pankaj Thakur; Satya Bir Singh; Jatinder Kaur (Kragujevac Journal of Science, 2014)
Steady thermal stresses in a rotating disc with shaft having density variation parameter subjected to thermal load have been derived by using Seth's transition theory. Neither the yields criterion nor the associated flow rule is assumed here. Results are depicted graphically. It has been seen that compressible material required higher percentage increased angular speed to become fully-plastic as compare to rotating disc made of incompressible material. Circumferential stresses are maximal at the outer surface of the rotating disc. With the introduction of thermal effect it decreases the value of radial and circumferential stresses at inner and outer surface for fully-plastic state.